Estimates of National Product 1960-61-1969-70 - Planning Commission (Planning Commission, 1971)
The estimates of national product have been prepared following generally the methodology described in the Brochure on Revised Series of National Product 1960-61 to 1964-65, but certain revisions have been carried out in view of the availability of fresh data. For the years prior to 1960-61, certain departures have become inevitable because of the nature and type of the data available for these years. The following paragraphs indicate briefly the changes in the procedure and source material used in the preparation of estimates by industry of origin and related aggregates.
Central Statistical Organisation Department of Statistic
Central Statistical Organisation Department of Statistic